A pyrolysis gasoline primary catalyst and a preparation method thereof

By preparing a catalyst containing an alumina and calcium phosphate composite support, the problems of existing cracked gasoline primary catalysts being prone to carbon buildup and being affected by impurities at high temperatures were solved, achieving high-activity and selective hydrogenation effects and extending the unit's operating cycle.

CN120421007BActive Publication Date: 2026-07-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410161141.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-05
Publication Date
2026-07-03
Estimated Expiration
2044-02-05

AI Technical Summary

Technical Problem

Existing pyrolysis gasoline catalysts are prone to carbon buildup at high temperatures, and precious metal catalysts are severely affected by impurities, leading to a shortened operating cycle. Non-precious metal nickel-based catalysts are prone to generating nickel-aluminum spinel that is difficult to reduce during the preparation process, affecting their activity.

Method used

A solution prepared using specific metal salts and additives is added during the alumina gelation process. Through good matching with the catalyst support, a catalyst containing an alumina and calcium phosphate composite support is prepared. Nickel is added as an active component, and a stable catalyst structure is formed through specific processes of molding and calcination, thereby improving hydrogenation activity and selectivity.

Benefits of technology

It improves the hydrogenation activity and selectivity of the catalyst, reduces carbon buildup, extends the operating cycle of the unit, and enhances resistance to impurities.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a pyrolysis gasoline primary catalyst and a preparation method thereof. The catalyst comprises an alumina and calcium phosphate composite carrier and a hydrogenation active component nickel, and the content of the nickel in the form of oxide is 10.0-25.0% based on the weight of the catalyst, the content of the calcium phosphate is 2.5-18.0%, and the content of the alumina is 57.0-87.5%; the total acid amount of the catalyst infrared acid is 0.45-0.75 mmol / g. The preparation method is as follows: (1) calcium oxide is added into the bottom water of a reactor, then an aluminum salt aqueous solution and a precipitating agent are added to carry out a gelation reaction, then phosphoric acid is added to carry out aging, and a filter cake is obtained; (2) the filter cake is pulped, then an active metal impregnation solution is added, and then an organic acid is added, so as to obtain active metal modified alumina dry gel powder; and (3) the active metal modified alumina dry gel powder of step (2), a peptizing agent and a extrusion aid are uniformly mixed, are extruded into a strip, and after drying and calcination, a catalyst product is obtained. The catalyst is applied to a pyrolysis gasoline primary selective hydrogenation process, and has high hydrogenation activity and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of clean refining technology, specifically relating to a primary catalyst for cracking gasoline and its preparation method. Background Technology

[0002] With the increase in new and expanded ethylene production capacity, the output of pyrolysis gasoline, a byproduct of ethylene cracking, is continuously increasing. This gasoline contains 60%–80% aromatics, including benzene, toluene, and xylene. Pyrolysis gasoline also contains dienes, monoolefins, alkenyl aromatics, sulfur, nitrogen, oxygen, chlorine, and heavy metals. The hydrogenation of pyrolysis gasoline can be divided into two stages. The first stage mainly involves saturated dienes, followed by monoolefins and a small amount of styrene. Diolefins in pyrolysis gasoline are prone to polymerization at high temperatures; therefore, the activity of the hydrogenation catalyst in the first stage should not be too high, requiring high selectivity for diene hydrogenation to reduce the strong exothermic reaction of monoolefin hydrogenation and accelerate carbon deposit formation.

[0003] In industrial applications, palladium catalysts, a precious metal, are often used for the selective hydrogenation of highly unsaturated hydrocarbons. However, these catalysts are significantly affected by impurities such as sulfur and arsenic, leading to shorter operating cycles. Non-precious metal nickel-based catalysts, on the other hand, have better market prospects due to their relatively better resistance to impurities and their price advantage.

[0004] Nickel catalysts are conventionally prepared using the impregnation method, which mostly involves preparing an impregnation solution with a soluble metal salt, performing 1-3 impregnation, drying, and calcination processes on a support, followed by reduction to obtain the catalyst. CN103769104A discloses a nickel-based selective hydrogenation catalyst, its preparation method, and its application. The nickel-based selective hydrogenation catalyst uses nickel as the active component and Al2O3 as the support. The catalyst contains 8-20 wt% NiO by weight of oxides, with the balance being Al2O3. The support is a mixed-phase support of θ-Al2O3 and δ-Al2O3. The active component nickel is still prepared using the conventional impregnation method with a soluble metal salt.

[0005] Compared to the conventional impregnation method, the kneading method eliminates the impregnation process, directly adding the active component during support molding. After molding, the catalyst is obtained through a single drying, calcination, and reduction process. However, the current kneading method suffers from the problem that nickel salts readily react strongly with the catalyst, forming nickel-aluminum spinel that is difficult to reduce, thus affecting the catalyst's activity. CN115990483A discloses a cracked gasoline hydrogenation catalyst, its preparation method, and its application. The catalyst includes a support and an active component, nickel. The support comprises alumina and silica, wherein the alumina contains α-phase alumina and θ-phase alumina. The active component, nickel, is added during support molding. The nickel source used is soluble nickel sources such as nickel nitrate, nickel acetate, and nickel sulfate. Inorganic or organic acids such as nitric acid, sulfuric acid, acetic acid, phosphoric acid, and citric acid are also added, resulting in a simple dissolution process. Although the above method improves the selective hydrogenation performance of the first-stage catalyst for cracked gasoline to some extent through changes in both the support and the preparation method of the active metal, further improvements are still needed. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a primary catalyst for cracked gasoline and its preparation method. The catalyst of this invention is added during the alumina gelation process using a solution prepared with specific metal salts and additives. Through good matching with the catalyst support, it is applied in the primary selective hydrogenation process of cracked gasoline, exhibiting high hydrogenation activity and selectivity.

[0007] The first-stage catalyst for cracked gasoline of the present invention comprises an alumina and calcium phosphate composite support and a hydrogenation active component, nickel. Based on the weight of the catalyst, the nickel content (calculated as oxide) is 10.0-25.0%, preferably 12.0-23.0%, the calcium phosphate content is 2.5%-18.0%, preferably 5.0%-16.0%, and the alumina content is 57.0%-87.5%, preferably 61.0%-83.0%. The total acidity of the catalyst in infrared radiation is 0.45-0.75 mmol / g, preferably 0.50-0.70 mmol / g, the L acid content is 0.40-0.70 mmol / g, preferably 0.35-0.65, and the Brønsted acid / L acid ratio is 0.07-0.25, preferably 0.08-0.20.

[0008] The pore volume of the primary catalyst for cracked gasoline of the present invention is 0.45~1.30 mL / g, and the specific surface area is 180~400 m². 2 / g.

[0009] The first-stage catalyst for cracked gasoline of the present invention may further include additives such as Ti, Zr, V, Cu, Zn, and Si. The additive content is 0.5% to 7% based on the total weight of the catalyst, and the sum of the contents of all components of the catalyst is 100%.

[0010] The method for preparing the first-stage catalyst for cracked gasoline of the present invention includes the following:

[0011] (1) Add calcium oxide to the bottom water of the reactor, and then add aluminum salt aqueous solution and precipitant in parallel to carry out the gelation reaction. After the gelation reaction is completed, add phosphoric acid to carry out the aging reaction. The aging product is washed and filtered to obtain filter cake.

[0012] (2) The filter cake obtained in step (1) is pulped, and then a solution containing basic nickel carbonate and citric acid is added to the pulp. Organic acid is added, and after stirring, the mixture is filtered and dried to obtain alumina dry adhesive powder with active metal modification.

[0013] (3) Mix the active metal modified alumina dry adhesive powder, adhesive solvent and extrusion aid from step (2) evenly, extrude into strips, and obtain the catalyst product after drying and calcination.

[0014] In the method of the present invention, the temperature of the bottom water in step (1) is 50~90℃, and the amount of bottom water added is determined according to the amount of reactants in the gelation reaction, which is generally well known to those skilled in the art.

[0015] In the method of the present invention, the aluminum salt in step (1) is an aqueous solution of aluminum sulfate, and the concentration of the aqueous solution of aluminum sulfate is 4~12g / 100mL based on aluminum oxide; the precipitant is an aqueous solution of sodium aluminate, and the concentration of the aqueous solution of sodium aluminate is 12~40g / 100mL based on aluminum oxide.

[0016] In the method of the present invention, the gelation reaction conditions in step (1) are: time of 0.4 to 1.5 hours and pH value of 7.0 to 9.5.

[0017] In the method of the present invention, the amount of phosphoric acid added in step (1) to convert all the calcium sulfate in the gelling product into calcium phosphate generally accounts for 1.6% to 12% of the weight of alumina in the gelling product.

[0018] In the method of the present invention, the aging reaction time in step (1) is 0.2 to 1 hour.

[0019] In the method of this invention, the washing in step (1) generally involves washing with deionized water until SO4 is reached. 2- ≤2.5%, Na + ≤0.05%, Fe 3+ If the concentration is less than 0.25%, it generally requires 2-5 washes.

[0020] In the method of the present invention, in the solution containing basic nickel carbonate and citric acid in step (2), the molar ratio of basic nickel carbonate to citric acid is 1.5 to 1.0.

[0021] In the method of the present invention, the organic acid added in step (2) is one or more of citric acid, lactic acid, glycolic acid, ethylenediaminetetraacetic acid, etc., and the amount added is 2.0 to 4.0 times the molar content of basic nickel carbonate.

[0022] In the method of the present invention, the stirring time in step (2) is 0.2 to 1 hour.

[0023] In the method of the present invention, the drying conditions in step (2) are: drying temperature 90~130℃, drying time 5~34 hours.

[0024] In the method of the present invention, the extrusion aid in step (3) can be one or more of guar gum powder, cellulose, starch, polymeric surfactant, etc., and the amount used accounts for 0.1% to 20.0% of the dry basis weight of the alumina dry adhesive powder containing active metal in step (2); the adhesive solvent can be one or more of aluminum sulfate, citric acid, nitric acid, acetic acid, oxalic acid, etc., and the amount used accounts for 0.1% to 20.0% of the dry basis weight of the alumina dry adhesive powder in step (2).

[0025] In the method of the present invention, the drying and calcination conditions in step (3) are as follows: drying at 100~120℃ for 1~5 hours and calcining at 350~550℃ for 1~5 hours.

[0026] The application of the first-stage catalyst for cracked gasoline of the present invention in the first-stage selective hydrogenation process of cracked gasoline.

[0027] The catalyst of this invention first undergoes a neutralization reaction of alumina in an environment where calcium oxide undergoes an exothermic hydration reaction. Calcium hydroxide, formed from the calcium oxide hydration reaction, serves as a seed crystal in the neutralization reaction solution. During the formation of the alumina dry gel, calcium sulfate precipitate is simultaneously generated. After neutralization, phosphoric acid is added for aging, converting calcium sulfate to calcium phosphate. Simultaneously, the total acidity of the support, especially the L-acid content, is significantly increased, forming a thiophilic support with L-acid centers, thus enhancing the catalyst's hydrogenation capacity. Using this method, the calcium component added in seed form can form a stable structure with alumina. The presence of calcium phosphate inhibits the formation of the NiAl₂O₄ phase and increases the Ni content. 2+The number of ions; This invention simultaneously uses a solution of basic nickel carbonate and citric acid in a certain proportion to form a nickel citrate complex, which is then added to an alumina slurry containing calcium phosphate. An organic acid is added to form a gel precipitate. During the subsequent calcination and decomposition process, the nickel citrate complex mixture forms a precipitate with the organic acid, ensuring uniform dispersion of the active component nickel in the alumina slurry. The added organic acid forms a gel precipitate, enhancing the directional and orderly dispersion of the active metal nickel during calcination. During the dispersion of the active metal, the presence of calcium phosphate weakens the interaction between the active metal and the support. The barrier effect of calcium phosphate on the active metal and alumina further increases the selective hydrogenation performance of the catalyst. Detailed Implementation

[0028] In this invention, the specific surface area and pore volume were determined using a cryogenic liquid nitrogen adsorption method, while the total acid content, Brønsted acid content, and Lewis acid content were determined using pyridine infrared adsorption spectroscopy. In this invention, % represents mass percentage. The catalyst composition was determined using a colorimetric method.

[0029] The catalysts used in this invention are described in detail below using examples. Example 1

[0030] First, add 4.2g of calcium oxide to 1L of water. Then, neutralize 600mL of aluminum sulfate aqueous solution and 200mL of sodium aluminate aqueous solution at 80℃ for 1.0h, controlling the pH of the neutralization reaction to be 8.8~9.0. Next, add 4.9g of phosphoric acid and age for 0.5h. After washing and filtering twice, a filter cake is obtained. The obtained filter cake is slurryed. 100mL of a mixed solution containing 30g of basic nickel carbonate and 32g of citric acid is added to the slurry. Then, 42g of citric acid is added and stirred for 0.5h. After filtration, the obtained filter cake is dried at 110℃ for 24h. After grinding, the catalyst dry gel powder is obtained. The dry gel powder is extruded and dried at 110℃ for 3h, and then calcined at 500℃ for 3h to obtain the finished catalyst A. Example 2

[0031] First, add 7g of calcium oxide to 1L of water. Then, neutralize 600mL of aluminum sulfate aqueous solution and 200mL of sodium aluminate aqueous solution at 80℃ for 1.0h, controlling the pH of the neutralization reaction to be 8.8~9.0. Next, add 8.17g of phosphoric acid and age for 0.5h. After washing and filtering twice, a filter cake is obtained. The obtained filter cake is slurryed. 100mL of a mixed solution containing 34g of basic nickel carbonate and 43g of citric acid is added to the slurry. Then, 35g of citric acid is added and stirred for 0.5h. After filtration, the obtained filter cake is dried at 110℃ for 24h. After grinding, the catalyst dry gel powder is obtained. The dry gel powder is extruded and dried at 110℃ for 3h, and then calcined at 500℃ for 3h to obtain the finished catalyst B. Example 3

[0032] First, add 4.2g of calcium oxide to 1L of water. Then, neutralize 600mL of aluminum sulfate aqueous solution and 200mL of sodium aluminate aqueous solution at 80℃ for 1.0h, controlling the pH of the neutralization reaction to be 8.8~9.0. Next, add 4.9g of phosphoric acid and age for 0.5h. After washing and filtering twice, a filter cake is obtained. The obtained filter cake is slurryed. 100mL of a mixed solution containing 38g of basic nickel carbonate and 53g of citric acid is added to the slurry. Then, 40g of citric acid is added and stirred for 0.5h. After filtration, the obtained filter cake is dried at 110℃ for 24h. After grinding, the catalyst dry gel powder is obtained. The dry gel powder is extruded and dried at 110℃ for 3h, and then calcined at 450℃ for 3h to obtain the finished catalyst C. Example 4

[0033] First, add 7g of calcium oxide to 1L of water. Then, neutralize 600mL of aluminum sulfate aqueous solution and 200mL of sodium aluminate aqueous solution at 80℃ for 1.0h, controlling the pH of the neutralization reaction to be 8.8~9.0. Next, add 8.17g of phosphoric acid and age for 0.5h. After washing and filtering twice, the resulting filter cake is slurried. Add 100mL of a mixed solution containing 42g of basic nickel carbonate and 47g of citric acid to the slurry, then add 53g of citric acid and stir for 0.5h. After filtration, dry the resulting filter cake at 110℃ for 24h. After grinding, the catalyst dry powder is obtained. The dry powder is extruded and dried at 110℃ for 3h, then calcined at 480℃ for 3h to obtain the finished catalyst D.

[0034] Comparative Example 1

[0035] Catalyst E was prepared using the same method as in Example 1, except that calcium oxide and phosphoric acid were not added.

[0036] Comparative Example 2

[0037] Catalyst F was prepared using the same method as in Example 3, except that 100 mL of an aqueous solution containing 79 g of nickel nitrate and 53 g of citric acid was added to the slurry.

[0038] Comparative Example 3

[0039] Catalyst G was prepared using the same method as in Example 1, except that 42g of citric acid was not added and stirred for 0.5 hours. Example 5

[0040] This example compares the physicochemical properties of the catalysts prepared in the above examples with the results of operating the above examples on a small-scale hydrogenation unit for 600 hours, as shown in Tables 1 and 2.

[0041] Table 1. Main properties of the catalyst

[0042] project A B C D E F G carrier properties <![CDATA[Ca3(PO4)2,wt%]]> 7.8 12.9 7.8 12.9 - 7.8 7.8 Total acid content in infrared radiation, mmol / g 0.572 0.613 0.572 0.613 0.237 0.572 0.572 B acid concentration, mmol / g 0.043 0.049 0.043 0.049 0.095 0.043 0.043 L-acid concentration, mmol / g 0.529 0.564 0.529 0.564 0.142 0.529 0.529 B / L ratio 0.081 0.087 0.081 0.087 0.67 0.081 0.081 Catalyst properties NiO, wt% 15 17 19 21 15 Loss Loss Pore ​​volume, mL / g 0.55 0.53 0.52 0.50 0.53 0.63 0.60 <![CDATA[Specific surface area, m 2 / g]]> 231 227 209 198 295 349 341

[0043] Table 2. Selective hydrogenation activity of catalysts

[0044] project crude oil A B C D E F G Diene, g iodine / 100g oil 25 1.4 1.1 1.0 0.9 6.0 - - Bromine value, g bromine / 100g oil 36 27 26 28 25 31 - -

[0045] Note: The reaction conditions were evaluated after catalyst reduction: P = 2.5 MPa; LHSV = 1.5 h. -1 H2 / Oil = 100 Nm 3 / m 3 ; Reaction temperature = 80℃.

[0046] The hydrogenation reaction test results in Table 2 show that the catalyst of this invention significantly reduces the diene content in cracked gasoline, and the olefins are slightly saturated. The catalyst of this invention exhibits excellent selective hydrogenation performance for dienes.

Claims

1. A naphtha primary catalyst characterized by: The catalyst comprises an alumina and calcium phosphate composite support and a hydrogenation active component, nickel. Based on the weight of the catalyst, the nickel content (calculated as oxide) is 10.0–25.0%, the calcium phosphate content is 2.5%–18.0%, and the alumina content is 57.0%–87.5%. The total infrared acid content of the catalyst is 0.45–0.75 mmol / g, the L acid content is 0.40–0.70 mmol / g, and the Brønsted acid / L acid ratio is 0.07–0.

25. The total infrared acid content, Brønsted acid content, and L acid content are determined by pyridine infrared adsorption spectroscopy. The preparation method of the first-stage catalyst for cracked gasoline includes the following... Content: (1) Add calcium oxide to the bottom water of the reactor, and then add aluminum salt aqueous solution and precipitant in parallel to carry out the gelation reaction. After the gelation reaction is completed, add phosphoric acid to carry out the aging reaction. Wash and filter the aging product to obtain filter cake; (2) Pulp the filter cake obtained in step (1), and then add a solution containing basic nickel carbonate and citric acid to the slurry. Add organic acid, stir, filter and dry to obtain active metal modified alumina dry glue powder; (3) Mix the active metal modified alumina dry glue powder, glue solvent and extrusion aid in step (2) evenly, extrude into strips, and after drying and calcination, obtain catalyst product.

2. The catalyst of claim 1, wherein: The catalyst has a pore volume of 0.45 to 1.30 mL / g and a specific surface area of 180 to 400 m 2 / g.

3. The catalyst of claim 1, wherein: The catalyst also includes one or more of Ti, Zr, V, Cu, Zn and Si promoters, with the promoter content being 0.5% to 7% by weight of the total catalyst, and the sum of the contents of all catalyst components being 100%.

4. A method for preparing a first-stage catalyst for cracked gasoline according to any one of claims 1 to 3, characterized in that... The following contents are included: (1) Add calcium oxide to the bottom water of the reactor, and then add aluminum salt aqueous solution and precipitant in parallel to carry out the gelation reaction. After the gelation reaction is completed, add phosphoric acid to carry out the aging reaction. Wash and filter the aging product to obtain filter cake; (2) Pulp the filter cake obtained in step (1), and then add a solution containing basic nickel carbonate and citric acid to the slurry, and then add organic acid. After stirring, filter and dry to obtain active metal modified alumina dry glue powder; (3) Mix the active metal modified alumina dry glue powder, glue solvent and extrusion aid in step (2) evenly, extrude into strips, and after drying and calcining, obtain catalyst product.

5. The method of claim 4, wherein: The aluminum salt mentioned in step (1) is an aqueous solution of aluminum sulfate, and the concentration of the aqueous solution of aluminum sulfate is 4~12g / 100mL based on aluminum oxide; the precipitant is an aqueous solution of sodium aluminate, and the concentration of the aqueous solution of sodium aluminate is 12~40g / 100mL based on aluminum oxide.

6. The method of claim 4, wherein: The gelation reaction conditions for step (1) are: time of 0.4 to 1.5 hours and pH value of 7.0 to 9.

5.

7. The method of claim 5, wherein: The amount of phosphoric acid added in step (1) is the amount that converts all the calcium sulfate in the gelling product into calcium phosphate.

8. The method of claim 4, wherein: The aging reaction time in step (1) is 0.2 to 1 hour.

9. The method of claim 4, wherein: In the solution containing basic nickel carbonate and citric acid described in step (2), the molar ratio of basic nickel carbonate to citric acid is 1.5 to 1.

0.

10. The method of claim 4, wherein: The organic acid added in step (2) is one or more of citric acid, lactic acid, glycolic acid and ethylenediaminetetraacetic acid, and the amount added is 2.0 to 4.0 times the molar content of basic nickel carbonate.

11. The method of claim 4, wherein: The stirring time in step (2) is 0.2 to 1 hour.

12. The method of claim 4, wherein: The drying conditions for step (2) are: drying temperature 90~130℃, drying time 5~34 hours.

13. The method of claim 4, wherein: The extrusion aid mentioned in step (3) is one or more of guar gum powder, cellulose, starch and polymeric surfactant, and its amount accounts for 0.1% to 20.0% of the dry basis weight of the active metal modified alumina dry adhesive powder; the adhesive solvent is one or more of aluminum sulfate, citric acid, nitric acid, acetic acid and oxalic acid, and its amount accounts for 0.1% to 20.0% of the dry basis weight of the active metal modified alumina dry adhesive powder.

14. The method of claim 4, wherein: The drying conditions for step (3) are: drying at 100~120℃ for 1~5 hours; the calcination conditions are: calcination at 350~550℃ for 1~5 hours.

15. The application of the first-stage catalyst for cracked gasoline according to any one of claims 1 to 3 in the first-stage selective hydrogenation process of cracked gasoline.

Citation Information

Patent Citations

  • Nickel base selective hydrogenation catalyst, preparation method and application thereof

    CN103769104A

  • Pyrolysis gasoline hydrogenation catalyst and preparation method and application thereof

    CN115990483A

  • Nickel-based hydrogenation catalyst and preparation method thereof

    CN106732620A

  • Production of hydrodesulfurization catalyst for hydrocarbon oil

    JP1997150059A